Does Banks’ Moratorium Alleviate the Burden of Borrowers? Case Of the Pandemic Covid-19 - Norsyameera Rosli; Anwar Allah Pitchay; Nik Hadiyan Nik Azman; Mohamad Isa Abd Jalil (Penerbit UMS, 2023)
The COVID-19 crisis has devastatingly affected the Small and Medium Enterprise (SMEs) cash flow. Subsequently, the employee was laid off as the SMEs could not sustain themselves. To address these issues, governments globally embrace moratoriums to alleviate the hardship. However, there is a clash between the borrowers' expectations, the government agenda, and the current banking system. Therefore, this study undertakes a study on why there is a need for Islamic financial institutions to undertake a similar approach to conventional banking in discharging their moratoriums. In addition, the study shall also suggest possible alternatives that would protect both the customers' and the Banks' interests while upholding Maqasid-Shariah. The study applies a case study approach. The primary data was collected through in-depth interviews. The applied thematic analysis (ATA) was then employed in analyzing the narrative provided by the participants. The findings conclude that the moratorium has met the borrowers' expectations regarding assisting during a difficult time. Meanwhile, practitioners concluded the positive impact of the moratorium on the borrowers only for the short term. Shariah executive has pointed out that providing a moratorium with entitlement for accumulated profit is justice for both borrowers and the Banks. The Islamic Financial Institutions have been discharging the moratorium according to Maqasid Shariah. The study reveals that the sustainability of the financial institutions depends on the accumulated profit collected as the Malaysian banking system is debt-based. Thus, the act of taking accumulated profit is deemed within the Maqasid Shariah. Effective communication, government intervention, and reevaluating the interest rate system calculation are possible alternatives to protect both customers and the banks should the moratorium be implemented again for a similar situation like the COVID-19 pandemic and lockdown.